(untitled) (Journal of the College of Education for Women, 2020)
The study aims to identify the degree of appreciation for the level of digital citizenship of a sample of Palestinian university students in the governorates of Gaza, and its relationship to the level of health awareness about the emerging coronavirus (covid-19). To achieve the objectives of the study, the researcher followed a descriptive approach by applying two questionnaires; the first, which consists of 30 items, was used to measure the level of digital citizenship. The second, which consists of 19 items, was used to measure the level of health awareness. Both questionnaires were applied on a sample of 367 students who were electronically selected using the manner simple randomness. Results have shown that the degree of appreciation for the level of digital citizenship was high with a relative weight of 76.08%. Besides, the level of health awareness of coronavirus was high with a relative weight of 81.83%. Additionally, it has been found that there is a direct relationship with a statistical significance between the degree of sample appreciation of the level of digital citizenship, and the degree of its evaluation of the level of health awareness of coronavirus, where the correlation coefficient was 0.468. Moreover, there has been shown that there are no statistically significant differences between the mean scores of the individuals appreciation of the level of health awareness of coronavirus (Covid-19) due to the gender variable. That is; the level of digital citizenship was in favor of females.The study recommended that e-university platforms should include health awareness messages for preventive purposes